Peacemakers : the Paris Conference of 1919 and its attempt to end war - MacMillan, Margaret 1943- (Murray, 2001)
"Between January and July 1919, after 'the war to end all wars', men and women from all over the world converged on Paris for the Peace Conference. At its heart were the leaders of the three great powers - Woodrow Wilson, Lloyd George and Clemenceau - but thousands of others came too, each with a different agenda. Kings, prime ministers and foreign ministers with their crowds of advisers rubbed shoulders with journalists and lobbyists for a hundred causes from Armenian independence to women's rights. Everyone had business in Paris that year - T. E. Lawrence, Queen Marie of Romania, Maynard Keynes, Ho Chi Minh. There had never been anything like it before, and there never has been since." "For six months the city was effectively the centre of world government as the peacemakers wound up bankrupt empires and created new countries. This book brings to life the personalities, ideals and prejudices of the men who shaped the settlement."--BOOK JACKET.